The Role of Data Analysis Using Artificial Intelligence Applications and Software in Evaluation and Guiding Financial Investment Decisions: The Case of ProPicks AI (Journal of Economic Additions, 2025)
This study seeks to underscore the significance of decision-making informed by financial assessments and strategic direction facilitated by artificial intelligence (AI) . The research employs data from ProPicks AI as a case study. One of the most important things the study found is that there are differences between the financial data that ProPicks AI gives and the financial reports of a group of companies that were studied.  ProPicks AI also tends to focus on how well tech companies are doing, which indirectly leads investors to this sector. The research indicates that AI technologies may surpass market performance,  although they face challenges in incorporating variables absent from their evaluation models.Jel Classification Codes: E 3, G11,F 1.
Keywords: Artificial Intelligence Applications and Software; Financial Data; Financial Investment decisions; ProPicks AI.